The proteomic landscape of Toxoplasma gondii extracellular vesicles across diverse host cell types - Cruz-Bustos, Teresa; Feix, Anna Sophia; Hummel, Karin; Schlosser, Sarah; Razzazi-Fazeli, Ebrahim; Joachim, Anja (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionExtracellular vesicles (EVs) are emerging as powerful tools used by pathogens to manipulate host cells, delivering molecular cargo that rewires cellular processes and the immune response. Toxoplasma gondii, a globally distributed parasite capable of infecting nearly all nucleated animal cells, uses this strategy to thrive in diverse host species and tissue environments.MethodsHere, we reveal the adaptability of T. gondii EVs through proteomic analysis of vesicles released from tachyzoites cultured in four different host cell types: human fibroblasts, green monkey kidney epithelial cells, mouse myoblasts and porcine intestinal epithelial cells.ResultsA core set of 1,244 proteins was consistently identified across TgEVs, defining a conserved signature. Beyond this conserved cargo, host-cell specific variation revealed how T. gondii fine-tunes EV content to exploit different cellular environments. Functional enrichment analyses revealed roles for TgEVs in targeting host protein synthesis and stress response pathways, with implications for immune evasion and infection spread.DiscussionThese findings provide insight into the potential role of EVs in host-pathogen interactions and help us understand the adaptive strategies used by T. gondii to survive and spread.